Analisis Rasio Likuiditas, Aktivitas dan Profitabilitas dalam Mengukur Kinerja Keuangan PT. Unilever Indonesia Tbk Periode 2021-2023 - Darmansyah Hegi Pranoto; Sungkono (CV. ITTC INDONESIA, 2024)
This study aims to determine, analyze, and explain the liquidity, activity, profitability and financial performance ratios of PT Unilever Indonesia Tbk in the 2021-2023 period. This type of research is descriptive research with a quantitative approach in the form of numbers or financial data obtained from financial statements and then interpreted the results of the financial performance of PT Unilever Indonesia Tbk for the period 2021-2023. The results of the study explain that the financial performance of PT Unilever Indonesia Tbk using the liquidity ratio is not good because it is below industry standards. The company needs to increase cash and reduce fixed assets in order to meet current liabilities that must be paid. As for financial performance using the ratio of activity and profitability as a whole in good condition because it is above industry standards. The conclusion of this study is that the company's financial performance is very important for owners, investors and the public so that they can assess whether the company's financial performance is in good condition or vice versa. The implication of this research is that good financial performance can make a sustainable business in the long term and give shareholders confidence in company management.